(untitled) (The Agriculturists, 2014)
This experiment was conducted in the farmers field to evaluate the performance of a modified planter machine for establishing direct seeded rice during aman and aus seasons in 2010 with four tillage treatments: (i) conventional tillage (CT) (ii) strip tillage (ST), (iii) bed formation (BP) and (iv) zero tillage (ZT). In later three treatments, seeding and fertilizer application was done simultaneously in a single pass operation by the planter. Flute type seed metering device was tested to study the seed dispensing rate, placement of seed and fertilizers. Minimum tillage saved fuel consumption by almost 25-46% and could represent a 27-48% cost saving in land preparation compared to CT. In addition to fuel savings, substantial time savings and additional benefits can be achieved. Seedling emergence was not affected by tillage options which indicated that seeds were placed at proper depth. Seed meter worked well to dispense rice seeds by maintaining actual seed rate. Seeds were not broken due to use of flute type seed metering device. Yields were not significantly different among the tillage treatments. BP showed the lowest benefit-cost ratio due to higher input cost as well as gross margin was lower compared to other tillage treatments. Strip tillage performed better than the other two minimum tillage methods compared to conventional method. Planter reduced seeding time, saved fuel and labour costs compared to conventional method and helped in timely sowing. Minimum tillage may be adopted to establish dry seeded rice in High Barind Tract. DOI: http://dx.doi.org/10.3329/agric.v11i2.17493 The Agriculturists 2013; 11(2) 87-95